Problems shaping the content of teaching materials in preparing future ecologists - Боголюбов, Володимир Миколайович (Eastern-European Journal of Enterprise Technologies, 2014)
The article deals with the methodology of content development of training materials for the preparation of the future environmentalists in the context of education for sustainable development taking into account the main production functions and typical tasks of the activity. Proposed to shape the content of teaching materials based on the content modules of education standards, which in turn should be developed on the analysis of production functions of future professionals with the principles of sustainable development. Developed the option structural and logical scheme of the educational process of future environmentalists training on the basis of disciplines of mathematics, natural sciences, professional and practical training cycles. Thus, the internal optimization of professional and practical training cycle must be accompanied by the strengthening of ties with other structural elements of the training content. Recommended to shape the content of scientific and teaching materials for each base core competence of future bachelor ecologist based on specific disciplines in which these competencies are to be covered on the basis of their interdisciplinarity in the context of the transition to sustainable development of society. Demonstrated the feasibility of upgrading the content of subjects of humanitarian and socio-economic training cycle with the content of subjects of professional and practical training with account of sustainable development principles. Established that the lack in educational and vocational training program for environmental disciplines such subjects as "Sociology", "Politics" and "Law" increases the content load on the base regulatory discipline "Philosophy" and leads to the need to expand its content with not typical educational elements.